Publicizing Performance - Strobl, Günter; Van Wesep, Edward D. (Management Science, 2013)
In most employment relationships, the employee's performance at the firm is privately, not publicly, observed. Firms can reward successful employees by publicizing their abilities, for example, via a job title, a glowing letter of recommendation, or a resume-worthy award. Firms that establish reputations for hiring young workers and promoting those who succeed lose good workers to competitors but can pay less to young, inexperienced workers in exchange. We find in a general equilibrium setting that firms with reputations for publicizing performance are able to pay less to employees at every level of tenure and thus earn economic profit, but that these firms will never be the most productive in the economy. For such equilibria to exist, the worker–firm match must be important, suggesting that this practice takes place only in human-capital-intensive industries. This paper was accepted by Wei Xiong, finance.